Toll-like receptor 9 polymorphisms in brazilian patients with systemic lupus erythematosus: a pilot study - Barbosa,L. M. (2023)
Abstract Toll-like receptor 9 (TLR9) is an important component of the innate immune system and have been associated with several autoimmune diseases, such as Systemic Lupus Erythematosus (SLE). The aim of this study was to investigate polymorphisms in TLR9 gene in a Brazilian SLE patients group and their association with clinical manifestation, particularly Jaccoud’s arthropathy (JA). We analyzed DNA samples from 204 SLE patients, having a subgroup of them presenting JA (n=24). A control group (n=133) from the same city was also included. TLR9 single nucleotide polymorphisms (SNPs) (−1237 C>T and +2848 G>A) were identified by sequencing analysis. The TLR9 gene genotype frequency was similar both in SLE patients and the control group. In the whole SLE population, an association between the homozygosis of allele C at position −1237 with psychosis and anemia (p < 0.01) was found. Likewise, the homozygosis of allele G at position +2848 was associated with a discoid rash (p < 0.05). There was no association between JA and TLR9 polymorphisms. These data show that TLR9 polymorphisms do not seem to be a predisposing factor for SLE in the Brazilian population, and that SNPs are not associated with JA.